External Validation of Endometriosis Fertility Index (EFI) in an Indonesian Population: A TwoCentre Prospective Study: Validasi Eksternal Endometriosis Fertility Index (EFI) pada Populasi Indonesia: Sebuah Studi Prospektif - Herbert Situmorang; Dimas Radityo (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To externally validate EFI in an Indonesian population. Methods: A prospective study was performed in 59 reproductive aged women diagnosed with both endometriosis and infertility who underwent laparoscopic surgery in Dr. Cipto Mangunkusumo and Carolus Hospital during the period of December 2012 to June 2016. Subjects were followed up for two years. Results: Statistical analyses suggested that younger age, infertility duration ï‚£ 3 years, higher LF score, and AFS score below 71 were significantly associated with pregnancy (p<0.001, p<0.001, p=0.035, p<0.001, respectively). Pregnant subjects had significantly higher median EFI score compared to the not pregnant group [EFI score 7 (5-9) vs 4 (1-8), p<0.001)]. Conclusion: Higher EFI score was significantly associated with higher pregnancy rate. [Indones J Obstet Gynecol 2017; 5-3: 160-163] Keywords: endometriosis, fertility, index, infertility, laparoscopy, pregnancy